PDE2 Inhibits PKA-Mediated Phosphorylation of TFAM to Promote Mitochondrial Ca2+-Induced Colorectal Cancer Growth - Zhao, Yilin; Wang, Yaya; Zhao, Jing; Zhang, Zhaohui; Jin, Mingpeng; Zhou, Feng; Jin, Chao; Zhang, Jing; Xing, Jinliang; Wang, Nan; He, Xianli; Ren, Tingting (Frontiers in Oncology, 2021)
Growing evidence indicates that the dysregulation of mitochondrial calcium (Ca2+) plays a critical role in the growth of tumor cells, including colorectal cancer (CRC). However, the underling mechanism is not fully elucidated. In this study, the regulatory effects of mitochondrial Ca2+ on calmodulin-dependent phosphodiesterase 2 (PDE2)/cAMP/PKA axis and the phosphorylation of mitochondrial transcription factor A (TFAM) as well as the growth of CRC cells were systematically investigated both in vitro and in vivo. Our findings demonstrated that MCU-induced mitochondrial Ca2+ uptake activated mitochondrial PDE2 in CRC cells. Activation of mitochondrial PDE2 significantly inhibited the activity of mitochondrial protein kinase A (PKA), which subsequently leads to decreased phosphorylation of TFAM. Our data further revealed that PKA regulates the phosphorylation of TFAM and promotes the degradation of phosphorylated TFAM. Thus, the suppression of PKA activity results in the accumulation of TFAM protein levels in mitochondria. Finally, our studies revealed that overexpression of TFAM significantly reversed the anti-tumor effects of MCU knockdown in CRC cells. Collectively, these data suggest that the mitochondrial Ca2+-activated PDE2/cAMP/PKA axis plays a key role in regulating TFAM stability and the growth of CRC cells.